Cardiovascular risks for participation in competitive sports among the adolescent athlete; who are attending selected sports medicine clinics in Sri Lanka - Pilot study - Dilanthika, N.P.M.; Senaratne, B.C.V.; Kandulawa, B.M.N.P.; Karunarathna, K.M.N.; Gunathilake, K.C.P.; Thebuwanarachchi, S.T.; Ruwanea, G.D.M.; De Silva, Y.H.S.; Thurairaja, C. (Proceedings of the Scientific Sessions, FMS, USJP 2015, 2015)
Attached

Objectives: The objectives were to determine the proportion of cardiovascular disease (CVD) among adolesi athletes who attend selected sports medicine clinics in Sri Lanka and to describe the clinical spectrum of C among adolescent athletes who attend selected sports medicine clinics in Sri Lanka. Methods: This cross-sectional study was conducted within six months in three sports medicine clinics(clusteri Colombo, Galle and Kandy and included all adolescent athletes aged 10-19years(n=566), who attended these du the said period for medical clearance prior to the competitive sports events. Secondary data was collected from pre-participation examination (PPE) forms using a data extraction form. Results: Prevalence of CVD among adolescent athletes in Sri Lanka was 1.5%. Most common cardiac abnorm; was Mitral Valve Prolapse(MVP). Mitral Stenosis, Ventricular Septal Defect(VSD) and Aortic Stenosis were c cardiac abnormalities detected. An important incidental finding of the study was the higher prevalence of (5°/c bronchial asthma among adolescent athletes. Conclusions: Prevalence of CVD among adolescent athletes in Sri Lanka is relatively low, but may lead to i outcomes if undetected early. Further research is needed to inform possible interventions to prevent he adversities arising from CVD irt adolescent athletes in Sri Lanka.